The conventional- notary municipal separation process - Zegarra Guzmán, Oscar (2012)
After the enactment in the year 2008 of the law which regulates the non-contentious procedure of the conventional separation and subsequent divorce in municipalities and notaries (Law 29227), the passing of time has shown us that despife the cited regulation represents a progress in the treatment and prompt solution to the problem of the conventional separation, there are also sorne Jactors and gaps in the application of separation that have not yet been corrected.